Inadvertent steroid injection into the crystalline lens - Alam, Md. Shahid (GMS Ophthalmol Cases, 2017)
Intravitreal triamcinolone is administered for a wide number of vitreoretinal conditions. Several complications including cataract formation, raised intraocular pressure, and endophthalmitis have been reported following intravitreal injections. We report a rare case wherein triamcinolone was inadvertently injected directly into the crystalline lens. A 41-year-old male presented to us with a history of intravitreal injection of triamcinolone in the left eye 2 weeks earlier. Slit lamp examination revealed a needle tract in the crystalline lens with steroid granules dispersed throughout the lens core. Such a complication is extremely rare with only three cases reported previously.